PREFERENCES OF YOUTH IN RELATION TO THE ORIGIN OF BRANDS - ROMANIAN AND FOREIGN - AND ITS MAIN MOTIVATION - Timiras, Laura Catalina (Studies and Scientific Researches. Economics Edition, 2016)
This paper is based on some results of a direct research conducted among youth 18-30, students of the Faculty of Economic Sciences of the Vasile Alecsandri University of Bacau. The research was conducted in the month of April 2016 on a sample of 100 students selected by group sampling scheme and has an exploratory character offering a guideline on youth preference for Romanian or foreign brands for product categories: food products, alcohol beverages, personal hygiene products, cosmetics, cleaning products, clothing, footwear, consumer electronics and cars. They are also shown and the main reasons underlying preferences in terms of brand origin. The results of study highlights that the youth prefer in a greater extent Romanian food products compared to foreign ones, but, for products encompassing high technology (cars, appliances and electronics) and for fashion products (clothing and footwear) over 50% of respondents prefer foreign brands.